2016
DOI: 10.1111/bjh.14194
|View full text |Cite
|
Sign up to set email alerts
|

Advances in understanding the mechanisms of erythropoiesis in homeostasis and disease

Abstract: Summary Anaemia or decreased blood haemoglobin is the most common blood disorder often characterized by reduced red blood cell (RBC) numbers. RBCs are produced from differentiation and commitment of haematopoietic stem cells to the erythroid lineage by a process called erythropoiesis. Coordination of erythropoietin receptor signalling with several erythroid transcription factors including GATA1 is essential for this process. A number of additional players that are critical for RBC production have been identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 121 publications
(173 reference statements)
0
36
0
Order By: Relevance
“…The diversity of mature blood cells derives from a common progenitor, the hematopoietic stem cell (HSC), which undergoes a series of commitment and differentiation steps in response to specific stimuli in specialized tissue microenvironments (e.g., bone marrow and thymus), to generate not only the circulating blood cells (white blood cells, red blood cells, and platelets), but also the immune and nonimmune organ resident immune cells . Among the circulating blood cells, the highly specialized, oxygen‐carrying, enucleated erythroid (red blood) cells must be produced daily at high rates, according to a very specialized and well‐characterized cell differentiation program, which includes progressive size reduction, cell cycle arrest, massive synthesis of globin chains, and enucleation . In this respect, GATA1 has been acknowledged as the master transcriptional regulator of erythropoiesis, controlling all aspects of differentiation, survival, and cell cycle arrest .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity of mature blood cells derives from a common progenitor, the hematopoietic stem cell (HSC), which undergoes a series of commitment and differentiation steps in response to specific stimuli in specialized tissue microenvironments (e.g., bone marrow and thymus), to generate not only the circulating blood cells (white blood cells, red blood cells, and platelets), but also the immune and nonimmune organ resident immune cells . Among the circulating blood cells, the highly specialized, oxygen‐carrying, enucleated erythroid (red blood) cells must be produced daily at high rates, according to a very specialized and well‐characterized cell differentiation program, which includes progressive size reduction, cell cycle arrest, massive synthesis of globin chains, and enucleation . In this respect, GATA1 has been acknowledged as the master transcriptional regulator of erythropoiesis, controlling all aspects of differentiation, survival, and cell cycle arrest .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Among the circulating blood cells, the highly specialized, oxygen-carrying, enucleated erythroid (red blood) cells must be produced daily at high rates, according to a very specialized and well-characterized cell differentiation program, which includes progressive size reduction, cell cycle arrest, massive synthesis of globin chains, and enucleation. [5][6][7] In this respect, GATA1 has been acknowledged as the master transcriptional regulator of erythropoiesis, controlling all aspects of differentiation, survival, and cell cycle arrest. 8,9 Maintaining GATA1 protein homeostasis has been shown to be a highly regulated process in erythropoiesis, with deregulation being a major factor in ineffective erythropoiesis or leukemic transformation in hematological disease.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of drugs affecting both the oxidative stress and the iron overload can give an effective outcome. Forkhead-box-O3 (Foxo3) is a critical transcription factor that protects the cell from oxidative stress by upregulating antioxidant enzymes during early stages of erythropoiesis [50]. At early stages, Foxo3 is phosphorylated by proteins of the EPOR-P13K/AKT/mTOR signaling pathway and is translocated out of the nucleus, where it remains inactivated.…”
Section: Dysregulation Of Iron Homeostasis In β-Thalassemia Diseasementioning
confidence: 99%
“…[1][2][3] Thus, recombinant human erythropoietin (rHuEpo) is the most widely used cytokine for treating anemia, especially in chemotherapy-induced anemia. There is an intricate network of interactions between various humoral factors and cytokines regulating the production of RBCs.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, this results in the proliferation and terminal differentiation of erythroid precursor cells and provides protection from RBC precursor apoptosis. [1][2][3] Thus, recombinant human erythropoietin (rHuEpo) is the most widely used cytokine for treating anemia, especially in chemotherapy-induced anemia. 4 However, a number of studies have demonstrated that Epo treatment compromises overall survival rate, and EpoR is expressed in various types of cancer cells 5 such as breast cancer, 6 gastric adenocarcinoma, 7 and melanoma.…”
Section: Introductionmentioning
confidence: 99%